2012
DOI: 10.5142/jgr.2012.36.4.369
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Ginsenoside Re Isolated from Ginseng Berry on Histamine and Cytokine Release in Human Mast Cells and Human Alveolar Epithelial Cells

Abstract: The berry of Panax ginseng significantly inhibited the histamine releases at the concentration of 30 μg/mL (p<0.05) and 10 μg/mL (p<0.01). The ginsenoside Re from ginseng berry was found out to have a potent effect in the experiment of histamin and cytokine release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
(18 reference statements)
2
14
0
Order By: Relevance
“…During inflammatory and allergic responses, mast cells activated by allergens release several inflammatory mediators, such as histamine, proinflammatory cytokines, and chemokines. Ginsenoside Rb1, Re, and Rh1 treatment significantly decreased histamine release from activated mast cells [28], [29], [30]. In addition, G-Rg5 and G-Rh3 suppressed degranulation of mast cells by decreasing histamine, TNF-α, and IL-6 in RBL-2H3 cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…During inflammatory and allergic responses, mast cells activated by allergens release several inflammatory mediators, such as histamine, proinflammatory cytokines, and chemokines. Ginsenoside Rb1, Re, and Rh1 treatment significantly decreased histamine release from activated mast cells [28], [29], [30]. In addition, G-Rg5 and G-Rh3 suppressed degranulation of mast cells by decreasing histamine, TNF-α, and IL-6 in RBL-2H3 cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenoside is the biochemically and pharmacologically active ingredient in ginseng [ 26 ]. Pharmacologically, ginsenoside acts like an anti-diabetic and anti-hypertensive, promotes liver function, cures hangovers, has an anti-fatigue, antioxidant, and anti-inflammatory activity, promotes protein synthesis, and has an immuno-enhancing effect [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that other effects of ginseng berries include such physiologically activating functions as antidiabetic [2], antiobese [2], Antisenility [3], antistress [4], antiallergic [5], and anticancer effects [6].…”
mentioning
confidence: 99%